Efektifitas Layanan Informasi Untuk Meningkatkan Kemampuan Manajemen Stres Siswa - Choli Astutik (Proceedings of The ICECRS, 2018)
Stress management can be defined as steps or efforts made someone to be able to manage the stress that was being endured. To help learners who are experiencing stress, a teacher of BK is expected provide information about how to control stress in order not to become smokers and use illegal drugs as an escape when it has a problem. The goal in this research is to know the effectiveness of information services in stress management improve the ability of students. To find out the factors supporting and restricting information services in improving the ability of stress management students. The research method used was an early experiment with One Group pretest-postest. While the design of the research is quantitative. The population in this research totalled 40 grade X SMA NU Sumenep, and the sample is 19 students. Based on the results of the analysis in the research on the effectiveness of information services to improve stress management grade X SMA NU SUMENEP, it can be concluded that tidad there are significant effects between information services against the level of stress management abilities.